Ethnological Research of (Traditional) Medicine in Southeastern Europe - Bukovčan, Tanja (Array, 2005)
Ethnomedicine, medical anthropology and folk medicine are some of the disciplines which deal with different topics related to traditional medicine and the cross-cultural concepts of health and illness. Both ethnomedicine and medical anthropology were established as disciplines during the 1960-ies and 1970-ies, when the majority of the medical projects offered to non-Western societies and Third World countries have failed. It became obvious that medical concepts have to be treated as cultural concepts and as parts of a single culture. Today the two disciplines deal with current ethnomedical problems in both Western and non-Western societies, among rural and urban population alike, and their findings are increasingly recognized as vital not only for cultural research, but also as the solutions to many practical, urgent and current problems of health care and prevention of disease. The research on the traditional concepts of health and illness in the region of South Eastern Europe was structured around the term ‘ folk medicine’ , which has been presented as a ‘ manifestation of cosmology’ . The majority of research dealt with the beliefs and customs connected to traditional healing and with their mythological background. Publications on these topics were descriptive ethnographies, which aimed only at the collection of data about the ‘ exotic’ healing rituals in rural areas, and, lacking any severe analysis, completely neglected the biological aspects of healing techniques. This paper aims at showing, using the history, development and current trends of traditional medicine in Croatian ethnology as a case study, the need to 'infest' the descriptive ethnographies on health and ilness with medical anthropological theories, thus moving away from magico-ritual concepts and including pragmatical research on 'how medical anthropology can alleviate human suffering (Joralemon:1999)'.